Studies on the influence of some psychoactive drugs on brain histamine. - Henwood, R. W. (University of Ottawa (Canada), 1977)
A major emphasis of research in mental health and neuropharmacology has been placed upon putative neurotransmitters. Histamine has received less attention until now partly due to difficulties encountered in measuring its concentration and turnover rates in discrete brain regions of rats. The enzymatic-isotopic assay procedures currently employed now afford accurate and reliable estimates in various brain regions of rats. Acute treatment with morphine, methadone, or naloxone did not induce any significant changes in the endogenous histamine concentrations in the hypothalamus, midbrain or cortex. Endogenous brain histamine concentrations have been found to be reduced in the hypothalamus, midbrain, and cortex following chronic morphine administration and these results are exacerbated by withdrawal. The metabolizing enzyme, histamine methyltransferase, was discovered to have unaltered activity after such treatments and the activity of the synthesizing enzyme histidine decarboxylase has been reported to be enhanced. These findings leave interference with precursor availability, impairment of histamine storage, increased release, or enhancement of an alternative metabolic pathway as explanations for the decreases noted in endogenous histamine concentrations. The decreases in brain histamine observed following chronic morphine administration could be prevented or reversed by simultaneous chronic administration of histidine. Acute and chronic pentazocine administration have been found to produce changes in brain histamine concentrations in a fashion parallel to the effects of morphine although qualitatively reduced. Mandrax and its compoments methaqualone and diphenhydramine were found to induce decreases in endogenous brain histamine concentrations in the brain regions investigated but these changes were less severe and shorter-lived following cessation of treatment than the changes noted following chronic morphine treatment. Chronic amphetamine administration produced a qualitatively different pattern of changes in brain histamine levels from that seen following the sedatives. Hypothalamic histamine was reduced and midbrain and cortical histamine levels were increased significantly. Tetrahydrocannabinol, either acutely or chronically, did not induce any detectable changes in brain histamine levels in the brain regions investigated. The sedative agents clearly depressed and the central stimulants significantly elevated the locomotor activities of the rats in these studies in a dose-dependent manner. The relationships between endogenous brain histamine concentrations or changes therein and spontaneous locomotor activities have been discussed. The current studies illustrate that histamine may be involved in the abnormal behavioral states induced by the psychoactive drugs used in these studies as has been proposed for other biogenic animes.
Keywords: Biology, Neuroscience.